Summary of a study of small and medium industries in Sarawak / Iris Syawe Seh Ling ... [et al.] - Ling, Iris Syawe Seh; Amin, Nicholas; Yap, Yin; Abu Shah, Ibrahim; Chan, Soon Huat (Biro Penyelidikan dan Perundingan, Institut Teknologi MARA, 1994)
The study attempts to provide a clear scenario of the manufacturing establishments in terms of their profile, production, marketing, manpower and training. It also gives insight into the entrepreneurs' profile, the impact of the stimulatory assistance or services and the problems faced by the Small and Medium Industries (SMIs).